Triagem Auditiva Neonatal: análise da cobertura, número de profissionais, disponibilidade de equipamento e qualidade do programa de triagem auditiva neonatal - Oliveira, Thalita da Silva (2020)
Introduction: the detection and early intervention of hearing disorders is still the best way to improve the prognosis of children who have some type of hearing impairment during childhood, for this, the presence of the professional responsible for neonatal hearing screening and proper functioning is necessary of the neonatal hearing screening program. Objective: (1) To verify the coverage of neonatal hearing screening and its association with the number of Speech Therapists in SUS and of equipment available in the Brazilian units in Brazil in the years 2012 and 2018 (2) to analyze the results of neonatal hearing screening and the rates of quality proposed by the Joint Committee of Infant Hearing (JCIH) and Guidelines for Neonatal Hearing Screening of the Ministry of Health of Brazil in a Neonatal Hearing Screening Program. Methodology: (1) The study is a descriptive ecological type of time series with the unit of analysis being the Federation Units of Brazil and the live births. (2) The study is of the secondary, transversal and descriptive type. A survey of the database of newborns who underwent neonatal hearing screening, including testing and / or retesting, was carried out in the period from 2016 to 2018. Conclusion: (1) The coverage of the screening showed an increase in Brazil, but still below the recommended and is related to the increase in the inclusion of speech therapists in SUS. The spatial distribution is heterogeneous throughout its territory. (2) The Neonatal Hearing Screening Program in João Pessoa is not in accordance with some quality criteria proposed by the JCIH and the Brazilian Ministry of Health, in addition, the lack of a unified computerized database makes it difficult to access the record of the results of the audiological procedures, as well as monitoring children screened and sent to other institutions in order to carry out the diagnosis and / or auditory monitoring.